The role of melatonin in maintenance of immunological internal environment - Al-Azawi, T. S. S.; Injidi, Majid H.; Rh,adi, A. K. J.; Habib, A. A.W. (The Iraqi Journal of Veterinary Medicine, 2003)
Melatonin hormone secretes from the pineal gland during dark period. This study was designed to investigate the effect of daily melatonin administration to chicks on some physiological parameters A total of fifty fawbro chicks of one day old were divided into two groups. The first group was given melatonin orally at a dose of 12ug/100g body weight daily for eight weeks and the other group was used as a control. During this experimental work the following parameters were studied. Daily feed and water intake, body temperature before and after melatonin administration with a general observation of chick’s behaviour. Blood samples were collected weekly to study some parameters (total red blood cells, hemoglobin content, packed cell volume and differential leukocytic count). The results showed that, melatonin caused a drop of body temperature with relaxation and sleeping of chicks up to three hours after its administration. This period was accompanied by depression of feed and water intake. Total RBCs count, Hb, PCV, and lymphocytes were significantly increased with a decrease in heterophil / lymphocyte ratio. In conclusion, results of this investigation indicate that melatonin causes calming and sleeping of chicks and improves their feed conversion ratio.These results appear to be the first indication that melatonin does play an important role in immunity and improvement of blood picture. These effects were suggested to be due to the immuno – enhancing and anti-stress actio melatonin.